The Emerging Role of Stress Granules in Hepatocellular Carcinoma - Dobrochna Dolicka (International Journal of Molecular Sciences, 2021)
Stress granules (SGs) are small membrane-free cytosolic liquid-phase ordered entities in which mRNAs are protected and translationally silenced during cellular adaptation to harmful conditions (e.g., hypoxia, oxidative stress). This function is achieved by structural and functional SG components such as scaffold proteins and RNA-binding proteins controlling the fate of mRNAs. Increasing evidence indicates that the capacity of cells to assemble/disassemble functional SGs may significantly impact the onset and the development of metabolic and inflammatory diseases, as well as cancers. In the liver, the abnormal expression of SG components and formation of SG occur with chronic liver diseases, hepatocellular carcinoma (HCC), and selective hepatic resistance to anti-cancer drugs. Although, the role of SG in these diseases is still debated, the modulation of SG assembly/disassembly or targeting the expression/activity of specific SG components may represent appealing strategies to treat hepatic disorders and potentially cancer. In this review, we discuss our current knowledge about pathophysiological functions of SGs in HCC as well as available molecular tools and drugs capable of modulating SG formation and functions for therapeutic purposes.